Draft Five Year Plan 1978-83 Co-operation Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
During Five Year Plan recess period, three annual plan for the year 1966-67, 1967-68 and 1968-69 were implemented. Financial outlay for these years was Rs.149.95 lakhs, Rs.137.31 lakhs & Rs.130.00 lakhs respectively.
Government of Madhya Pradesh, Planning, Economics and Statistics Department